Why don't women rule the world? : understanding women's civic and political choices - Jenkins, Shannon...[et. all.] (London Sage, 2020)
"Why don't women rule the world, and why don't they have more influence over the way the world is structured? This book begins to explore this question by looking at how underrepresentation of women manifests comparatively and also by exploring how it plays out in policy. Why Don't Women Rule the World? is written by 4 high-profile leaders who teach, publish and head up national and international academic caucuses on Women and Politics. They have collaborated on a project that not only offers grounded theory with practical job-related activities; but, also with an important comparative politics perspective. The book distinguishes itself from other Women and Politics texts due to three unique features: First, each chapter explores concepts from not only a U.S. perspective, but also a comparative one, expanding students' awareness of their own intersectional identities and the varying effects of patriarchy on women worldwide. Second, each chapter also has a policy feature, focusing on one or two policy areas allowing students to see the ways in which theories and concepts discussed in the chapter manifest in their lives. Finally, each chapter includes a political engagement feature with activities and prompts purposefully intended to bolster political interest, efficacy, and ambition. The book provides a thorough and theoretical introduction to the study of Women and Politics, while also meeting the growing demand for higher education to play a more prominent role in bolstering students' political interest, ambition and efficacy"--
Includes bibliographical references and index.
Keywords: Women political activists; Leadership in women; Male domination (Social structure)